2017
DOI: 10.1039/c7an00985b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in phosphoproteomics and application to neurological diseases

Abstract: Phosphorylation has an incredible impact on the biological behavior of proteins, altering everything from intrinsic activity to cellular localization and complex formation. It is no surprise then that this post-translational modification has been the subject of intense study and that, with the advent of faster, more accurate instrumentation, the number of large-scale mass spectrometry-based phosphoproteomic studies has swelled over the past decade. Recent developments in sample preparation, phosphorylation enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 227 publications
(224 reference statements)
0
29
0
Order By: Relevance
“…This results in a rather high demand for material compared to proteomics, which can hinder the employment of phosphoproteomics. For quantification, metabolic or chemical labeling is frequently employed, but label-free approaches are available as well (Arrington et al 2017). Current phosphoproteomics studies identified up to 20000 phosphorylation sites (von Stechow et al 2015).…”
Section: Which Omics Layers To Use For Toxicological Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a rather high demand for material compared to proteomics, which can hinder the employment of phosphoproteomics. For quantification, metabolic or chemical labeling is frequently employed, but label-free approaches are available as well (Arrington et al 2017). Current phosphoproteomics studies identified up to 20000 phosphorylation sites (von Stechow et al 2015).…”
Section: Which Omics Layers To Use For Toxicological Research Questionsmentioning
confidence: 99%
“…Many signaling pathways include phosphorylation reactions and an association of these phosphorylation sites to the pathways is readily possible. Other phosphorylation sites require additional experiments to associate them to a specific kinase and thus to a pathway (Arrington et al 2017).…”
Section: Which Omics Layers To Use For Toxicological Research Questionsmentioning
confidence: 99%
“…There are many types of PTMs, including phosphorylation, methylation, palmitoylation, glycosylation, acetylation, SUMOylation, ubiquitination, and S-nitrosylation. Phospho-proteomics can map differential phosphorylation of kinases and phosphatases and their substrates, and it has been used to identify novel altered pathways in AD, ASD, and other neurological disorders [47]. For example, investigation of the phospho-proteome in AD cell line models and post-mortem brain samples has revealed the involvement of specific kinases in heat shock proteindependent protein folding, insulin-mediated signaling, p53 regulation, and neuronal autophagy [48][49][50].…”
Section: Identifying and Quantifying Post-translation Modificationsmentioning
confidence: 99%
“…The abnormal activity of protein kinases may induce several human diseases [6][7][8]. Especially, it has been found that there are lots of highly sensitive and specific phosphorylated proteins or peptides in the body fluids or tissues from cancer patients, indicating that phosphorylation by the specific kinase is closely related to the occurrence and development of cancers [9][10][11][12]. Various assay systems, including mass spectrometry [13], radioactivity [14], immunoprecipitation [15], fluorescence [16][17][18][19], colorimetry [20], and electrochemistry [21][22][23] based methods, have been developed for the detection of protein kinases and the corresponding phosphorylated substrates.…”
Section: Introductionmentioning
confidence: 99%